The case of an 85‐year‐old female with acute right hemiparesis with status epilepticus - Thunyares Sripan; Wanakorn Rattanawong (Annals of Clinical and Translational Neurology, 2022)
An 85-year-old right-handed woman with a known history of type 2 diabetes mellitus, essential hypertension, and dyslipidemia presented to our emergency department due to progressive right hemiparesis and motor aphasia for 2 days. At the emergency department, the patient developed a generalized tonic–clonic seizure which lasted for 2 minutes. She did not gain consciousness afterwards and was intubated and was admitted to an intensive care ward. At first, a left middle cerebral artery infarct was suspected. Computer tomography of the brain did not show abnormalities. Magnetic resonance imaging showed clusters of microbleeds and superficial siderosis in both hemisphere with white matter hyperintensities surrounding these areas. Cerebral amyloid angiopathy-related inflammation was suspected. Electroencephalography showed that she was in nonconvulsive status epilepticus. Treatment with antiepileptic drugs and corticosteroids was effective in improving her symptoms. Possible cerebral amyloid angiopathy-related inflammation1, 2 with definite nonconvulsive status epilepticus3 and postictal Todds paralysis (Figure 1).
Keywords: Intracerebral and Subarachnoid Hemorrhage Research; Neurological and metabolic disorders; Alzheimer's disease research and treatments